ГЕНДЕР ТЕНГЛИК: ФИКРЛАР ВА МУЛОҲАЗАЛАР - Абдуллаева, Я.А. (SCIENCE and SOCIETY, 2021)
This article discusses gender equality. At the international level, the role and activities of women in society have been studied. The focus is on shaping a gender culture.
Keywords: gender; world; Central Asia; Uzbekistan; women; parliament; MP; gender culture; family